2020
DOI: 10.1111/cas.14553
|View full text |Cite
|
Sign up to set email alerts
|

Impact of DPYD, DPYS, and UPB1 gene variations on severe drug‐related toxicity in patients with cancer

Abstract: Cancer treatment with a fluoropyrimidine (FP) is often accompanied by severe toxicity that may be dependent on the activity of catalytic enzymes encoded by the DPYD, DPYS, and UPB1 genes. Genotype‐guided dose individualization of FP therapy has been proposed in western countries, but our knowledge of the relevant genetic variants in East Asian populations is presently limited. To investigate the association between these genetic variations and FP‐related high toxicity in a Japanese population, we obtained bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Further example of ethnic heterogeneity within the Japanese population has been demonstrated by Yokoi et al, who investigated DPYD variants in 301 patients undergoing FP-based chemotherapy (among other exploratory gene variants). 33 They found 15 DPYD variants, 7 of which were further evaluated in silico and were found to have probable pathogenic effects. Clinically, heterozygous carriers of each of these 7 variants developed grade 3 toxicities, including neutropaenia and/or diarrhoea and vomiting.…”
Section: Frequency Of Typical and Novel Dpyd Variants In Non-caucasian Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further example of ethnic heterogeneity within the Japanese population has been demonstrated by Yokoi et al, who investigated DPYD variants in 301 patients undergoing FP-based chemotherapy (among other exploratory gene variants). 33 They found 15 DPYD variants, 7 of which were further evaluated in silico and were found to have probable pathogenic effects. Clinically, heterozygous carriers of each of these 7 variants developed grade 3 toxicities, including neutropaenia and/or diarrhoea and vomiting.…”
Section: Frequency Of Typical and Novel Dpyd Variants In Non-caucasian Populationsmentioning
confidence: 99%
“…Grade 3 toxicity incidence in the remaining wild-type cohort was 17%, 50/294. 33 Yokoi identified that each pathogenic variant carrier was different and that this would pose an issue for pre-treatment screening panels in Japanese populations. Caucasian variants and others described within this review were also not detected in this Japanese cohort.…”
Section: Frequency Of Typical and Novel Dpyd Variants In Non-caucasian Populationsmentioning
confidence: 99%
“…Besides, for cancer patients, UPB1 was screened as a prognostic circulating biomarker or signature for patients with hepatocellular carcinoma ( 34 , 35 ), similar to clear renal cell carcinoma ( 36 ). In addition, for the treatment of specific tumors, especially the 5-fluorouracil treatment of colorectal cancer, some researchers explored the role of UPB1 in the 5-fluorouracil pathway or fluoropyrimidine-related high toxicity ( 37 , 38 ). What’s more, we not only introduced UPB1 in the clinical prognostic analysis of LUAD for the first time but also found the expression of UPB1 was correlated with CD8 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…The Clinical Pharmacogenetics Implementation Consortium (CPIC) and Dutch Pharmacogenetics Working Group (DPWG) have established guidelines on 5-FU dosage adjustment based on DPYD genetic polymorphisms ( Henricks et al, 2015 ; Amstutz et al, 2018 ; Lunenburg et al, 2020 ). However, there are considerable geographical-ethnicity differences in the variation and frequency of DPYD genetic polymorphisms, and these four DPYD risk variants have not been identified in Asian populations, including the Japanese population ( van Kuilenburg, 2004 ; Maekawa et al, 2007 ; Yokoi et al, 2020 ). We previously reported enzymatic functional alterations in 21 DPD variants identified by whole-genome sequencing (WGS) of 1,070 Japanese individuals, suggesting that some DPD variants specific to the Japanese population may be responsible for the development of severe 5-FU toxicity ( Hishinuma et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%